HISAB-RUKYAT SEBAGAI METODE PENETAPAN AWAL BULAN QOMARIYAH - Seff, Syaugi Mubarak (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2007)
Determining ahe beginning of Fasling and Icd Fkr is an impojlant matrer becausc it is related lo religious worship. At leasa rhere arc firce grcups which ha5 different opinion on how to determin the beginning ofFasting and ted Fitr, they are: a g.opu which is based or nrkyalul hilat, a gro$p which is baed on ijtirnaa', and a group uhich is based on hisab wujud at-hitaat. ln tndonesia, delrmining the Fasrjng month ,md Id fits is the r0sponsibiliry of the go!ernmenr i.e. rhe vini,rcr ofReliBious AlIair.